The Effect of Social Media Marketing Activities on Skintific Product Purchase Decision, with Mediation Social Media Influencers and Fear of Missing Out (FOMO) in Generation Z - Jayanti, Apriliya Dwi; Roosdhani, Mohamad Rifqy (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study analyzes the effect of Social Media Marketing Activities (SMMA) on Social Media Influence (SMI), Fear of Missing Out (FOMO), and Purchase Decision (PD) for Skintific products. Using a quantitative approach and the Partial Least Squares (PLS) method, data were collected from 120 active social media users who are Skintific consumers. Results show that SMMA directly affects SMI, FOMO, and PD, indicating that social media marketing can shape social influence, evoke FOMO, and drive purchases. While SMI did not mediate the SMMA and PD relationship, FOMO did, highlighting the role of consumer emotions in purchase decisions. These findings emphasize the effectiveness of urgency and exclusivity-based strategies in enhancing Skintific’s social media marketing impact.